PTU-074 Low-Dose Thiopurine and Allopurinol Co-Therapy Results in Significant Cost Savings at a District General Hospital. (4th June 2013) - Johnson, H E; Dewhurst, H M; Weaver, S A; McLaughlin, S D
Abstract : Introduction: Thiopurines are used for maintenance of remission in IBD. In England and Wales biologics are approved by NICE (National institute for health and clinical excellence) for Crohn's disease (CD) but not ulcerative colitis. Adalimumab is recommended in preference to infliximab in patients over 65kg due to cost. Published data report > 50% of patients stop thiopurines due to theraputic failure, hepatitis or side effects. In this situation most UK clinicians start biologics in CD patients. This has significant cost implications. An alternative treatment strategy is low dose thiopurine and allopurinol (LDTA) co-therapy which is effective in most patients who fail standard dose thiopurines. Some patients require liquid thiopurine to achieve the correct (low) dose -this formulation is significantly more costly than tablets. We report the annual cost savings from adopting this strategy at our centre. Methods: We maintain a prospective IBD database. Patients with CD treated with LDTA in preference to biologic therapy were identified. The annual drug costs of their treatment with LDTA compared with biologic therapy (adalimumab for patients over 65kg, infliximab for patients < 65kg) were calculated including the cost for the formulation of thiopurine used (liquid/capsule/tablets) and the dose prescribed. Costs of attending the day unit for an infusion were not included. Results: 17 CD patients who failed standard thiopurine and were eligible for biologics were identified over a 1 year period (Sept 2011-Sept 2012). Of these 4 (24%) failed LDTA and progressed to biologics, 13 (76%) entered a sustained clinical remission. Mean weight of patients = 77.3kg (range: 53.5–105), 6 (46%) patients required a liquid thiopurine. Mean calculated costs were: thiopurine £451.95 (range: £48.48-£1345.44). biologic: £11, 331 (range: £10, 560-£16, 081). Mean cost saving per patient: £10, 879 (range: £9, 215-£15, 146). Total cost saving: £141, 427. Conclusion: We have previously reported that low dose thiopurine and allopurinol co-therapy is safe and effective. In the present study we have identified significant annual cost savings can be made when this treatment strategy is used to prevent escalation to biologics. These cost savings are likely to be even more significant in the long term since a significant proportion of patients treated with biologic therapy require dose escalation. We believe adopting this strategy more widely could lead to significant health-care savings. Disclosure of Interest: None Declared